2014
DOI: 10.4028/www.scientific.net/amr.996.155
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Stress Profiles in Expanded Austenite by Combining Successive Layer Removal and GI-XRD

Abstract: Abstract. The present work deals with the evaluation of the residual-stress profile in expandedaustenite by successive removal steps using GI-XRD. Preliminary results indicate stresses of several GPa's from 111 and 200 diffraction lines. These stresses appear largest for the 200 reflection. The strain-free lattice parameter decayed smoothly with depth, while for the compressive stress a maximum value is observed at some depth below the surface. Additionally a good agreement was found between the nitrogen profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[8,28] Nevertheless, huge compressive stress levels in excess of 7 GPa as reported for nitrided AISI 316 cannot be understood and have recently been attributed to the application of inappropriate elastic constants and grain-interaction models. [29] B. Effect of Prior Deformation on Nitriding Behavior…”
Section: A Mechanical Properties and Microstructure Of As-deformed Mmentioning
confidence: 99%
“…[8,28] Nevertheless, huge compressive stress levels in excess of 7 GPa as reported for nitrided AISI 316 cannot be understood and have recently been attributed to the application of inappropriate elastic constants and grain-interaction models. [29] B. Effect of Prior Deformation on Nitriding Behavior…”
Section: A Mechanical Properties and Microstructure Of As-deformed Mmentioning
confidence: 99%
“…This may be caused by the weak Ni-N repulsion with slightly decreases the solubility of N in γ N (see in this respect [42][43][44], where it is observed that a high Ni content limits the N solubility in the alloys 2 ). These lattice parameter values are affected by both the composition and the occurrence of compressive residual stresses [45]. The lattice parameter of original alloys is also plotted in the Fig.…”
Section: Evolution Of Lattice Parameters In γ N and γ' Nmentioning
confidence: 99%
“…L 0 22 (41) Since there are now both a plastic region from the surface to a depth z pl and an elastic region from z pl to the maximum depth, L, the integral is split as follows Assuming constant material parameters (E, ν) and inserting the expressions for the stress in elastic (equation ( 39)) and the plastic regions (equation ( 38)) in equation ( 43) gives…”
Section: Plastic Accommodation Of Stressmentioning
confidence: 99%
“…Bottoli, et al [40] investigated two qualities of austenitic stainless steel deformed to various degrees of equivalent strain, and found that the Vickers hardness (HV) and yield stress Realizing that hardness and yield stress both are a measure of the resistance against plastic deformation, it is attempted to obtain an estimate for the concentration dependence of the yield stress from the hardness. Correlating hardness-depth and concentration-depth profiles for nitrided AISI 316 austenitic stainless steel from [41] and converting hardness into yield stress with Eq. A-15, the dependence displayed in Fig.…”
Section: A5-concentration Dependent Yield Stressmentioning
confidence: 99%